2017
DOI: 10.1177/1084822317700883
|View full text |Cite
|
Sign up to set email alerts
|

Applying User-Centered Design to Develop an Audit and Feedback Intervention for the Home Care Sector

Abstract: The objective of this study was to optimize a planned audit and feedback (A&F) intervention for home and community care through incorporating user-centered design principles. Phase 1 comprised the development of a paper prototype, followed by testing of the prototype using semistructured interviews and focus groups. Phase 2 involved the development of a revised and online prototype based on the results of Phase 1, followed by user testing. A total of 39 participants across Phase 1 (n = 33) and Phase 2 (n = 6) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Best practice guidance recommends the use of UCD to develop reports, including testing the recommended best practices themselves [3]. Studies of UCD applied to feedback report development are limited, but have demonstrated the use of iterative prototyping and user observation [8,13]. We build on these studies to contribute a method that incorporates key feedback report components and their dependencies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Best practice guidance recommends the use of UCD to develop reports, including testing the recommended best practices themselves [3]. Studies of UCD applied to feedback report development are limited, but have demonstrated the use of iterative prototyping and user observation [8,13]. We build on these studies to contribute a method that incorporates key feedback report components and their dependencies.…”
Section: Discussionmentioning
confidence: 99%
“…These methods can enable feedback report designers to recognize defects and improvement opportunities in both the form of the report (i.e., how information is displayed) and its content (i.e., what information is communicated). For example, UCD activities improved the design of feedback reports for home healthcare professionals regarding report colors (form) and regional performance comparisons (content) [13]. By repeatedly testing an artifact, a designer can further refine the design of a prototype until no significant problems are identified [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Informed by user-centred design methodology, usability testing is a technique to evaluate whether the intended users of a product or service can achieve desired tasks. In the context of the A&F literature, usability of the feedback report is an issue which is addressed infrequently, despite the proliferation of electronic feedback [2932]. Participants were encouraged to “think out loud” as they attempted to complete two distinct tasks on the D2D website [33].…”
Section: Methodsmentioning
confidence: 99%